Sexually Transmitted Diseases. - Beigi, Richard H. (John Wiley & Sons, 2012)
Sexually Transmitted Diseases present a major public health challenge. Over 25 diseases can be transmitted through sexual activity, and effective treatment, especially where long term infection can lead to further health problems, and in women infertility, requires good diagnostic skills and understanding of the best treatment methods. This book aims to give a practical guide to diagnosis and treamtent in a patient-centred framework, with care at the heart of the book. The aim of the Gynecology in Practice Series is to provide a clinical 'in the office' or 'at the bedside' guide to effective pa.